Fish consumption and heart rate variability - Hansen, Anita L.; Dahl, Lisbeth; Bakke, Lene; Frøyland, Livar; Thayer, Julian F. (Journal of psychophysiology, 2010)
The present study investigates the impact of seafood intake on biological markers in blood such as the marine very long-chain polyunsaturated omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), 25-hydroxyvitamin D (25(OH)D), in addition to heart rate variability (HRV), which is an important biological marker of good health, both physical and mental. A total of 53 male inmates from a Norwegian prison were randomly assigned to intervention and control groups, although attrition reduced some comparisons at the end of the study to 13 (intervention group (n = 6) and control group (n = 7). The intervention group received seafood (mainly fatty fish, > 8% fat) for dinner three times per week for a period of 6 months. Both groups were requested to eat their usual diet provided by the prison. Blood samples were collected and HRV (high frequency (HF) and low frequency (LF) power) was measured before and after the study period. Overall, the intervention group showed significant increase in levels of 25(OH)D and HF-power, and a significant reduction in the sympathovagal balance (LF/HF). The present findings may have important implications with regard to health improvement.
Online veröffentlicht: June 09, 2010
Gesehen am 08.03.2023